Project SCORE! Coaches` perceptions of an online tool to promote positive youth development in sport - Strachan, L.; MacDonald, D. J.; Côté, J. (International Journal of Sports Science & Coaching, 2016)
Research points to the potential of youth sport as an avenue to support the growth of particular assets and outcomes. A recurring theme in this line of research is the need to train coaches to deliberately deliver themes relating to positive youth development (PYD) consistently in youth sport programs. The purpose of the study was to design and deliver a technology-based PYD program. Project SCORE! (www.projectscore.ca) is a series of 10 lessons to help coaches integrate PYD into sport. Four youth sport coaches completed the program in this first phase of this research and were interviewed. The goal of this study was to gain some insights from coaches as they completed the program. Positive comments about the program (i.e. ease of use, success of particular lessons, coach`s personal growth) and challenges regarding teaching positive skills to youth are discussed. These results helped to shape the program and make necessary changes so that it may be used for a larger research study. Other implications and future research directions are discussed.